Leaf Functional Traits Diversity of Mango Wild Relatives (Mangifera spp.) - Fesy Antina; Kasrina; Vandra Kurniawan; Wiguna Rahman; Suluh Normasiwi (Jurnal Biodjati, 2025)
There are 69 species of Mangifera distributed worldwide, and approximately 35-40 of these species are found in tropical Asia. This widespread distribution naturally affects the functional characteristics of Mangifera species. This research aims to determine the variation in leaf functional traits of Mangifera species based on their subgenus (Mangifera and Limus) and the differences in elevation locations (Bogor Botanical Garden/lowland and Cibodas Botanical Garden/highland). The leaf's functional traits were measured through ten parameters: Fresh Weight (FW), Dry Weight (DW), Leaf Area (LA), Specific Leaf Weight (SLW), Specific Leaf Area (SLA), Leaf Dry Matter Content (LDMC), Chlorophyll Content (CC), Stomata Density (SD), Stomata Length (SL), and Stomata Width (SW). The observational data were analyzed using Pearson Correlation, One-Way ANOVA, and Post Hoc Test with Duncan’s Multiple Range Test (DMRT). The results showed differences in Mangifera species' leaf functional traits between subgenus and locations. It was observed that DW, LA, SLA, and CC were higher in the subgenus Mangifera than in the subgenus Limus. The results also show that the SLW, SLA, LDMC, and CC values are influenced by altitude. The differences in the functional traits of Mangifera species are driven by environmental factors that induce phenotypic changes through plasticity, reflecting their adaptation to different environments.